Structure-function properties of food proteins - Phillips, Lance G. (Food science and technology international series., 1994)
The functional properties of food proteins affect behavior in food systems and influence the quality attributes, structure, texture, mouth-feel, and flavor of the final product. These attributes are precisely those with which food engineers and technologists are concerned when developing new products. This innovative book provides an overview of the physical properties of proteins and how dynamic changes in conformation, structural changes, and protein-protein interactions are involved in the performance of particular functional properties such as gelation, emulsification, and foaming properties. Models used include B-Lactoglobulin, soy, and meat proteins.